Atherogenic dyslipidemia and risk of silent coronary artery disease in asymptomatic patients with type 2 diabetes: a cross-sectional study. Issue 1 (December 2016) - Valensi, Paul; Avignon, Antoine; Sultan, Ariane; Chanu, Bernard; Nguyen, Minh; Cosson, Emmanuel
Abstract Background To investigate whether atherogenic dyslipidemia, a dyslipidemic profile combining elevated triglycerides and low high-density lipoprotein (HDL) cholesterol, is predictive of risk of silent myocardial ischemia (SMI) or angiographic coronary artery disease (CAD) in asymptomatic patients with type 2 diabetes. Methods Cohort study in 1080 asymptomatic patients with type 2 diabetes with a normal resting electrocardiogram, at least one additional cardiovascular risk factor and low density lipoprotein (LDL) cholesterol <3.35 mmol/L. Patients initially underwent screening for SMI by stress myocardial scintigraphy. Patients with SMI underwent coronary angiography. Results Overall, 60 (5.5 %) patients had atherogenic dyslipidemia (triglycerides ≥2.26 mmol/L and HDL cholesterol ≤0.88 mmol/L). In multivariate analyses taking into account the parameters associated in univariate analyses with SMI and then CAD, atherogenic dyslipidemia was associated with SMI (odds ratio 1.8[1.0–3.3]), as were male gender (OR 2.1[1.5–2.9]), BMI (OR 0.97[0.94–0.997]), retinopathy (OR 1.4[1.1–1.9]), peripheral occlusive arterial disease (POAD: OR 2.5[1.6–3.8]) and mean blood pressure (OR 1.01[1.00–1.03]); atherogenic dyslipidemia was associated with CAD (OR 4.0[1.7–9.2]), as were male gender (OR 3.0[1.6–5.6]), BMI (OR 0.94[0.90–0.995]), retinopathy (OR 1.7[1.0–2.9], POAD (OR 4.0[2.1–7.4]) and mean blood pressure (OR 1.03[1.01–1.05]). In the subgroup of 584 patients with LDL cholesterol <2.6 mmol/L, atherogenic dyslipidemia was also associated with CAD (OR 3.6[1.5–9.0]). Conclusions Atherogenic dyslipidemia was associated with an increased risk of SMI and silent CAD in patients with type 2 diabetes and LDL cholesterol levels <3.35 mmol/L. Specific management of atherogenic dyslipidemia might help reducing the high residual burden of cardiovascular disease.